HUBUNGAN KUALITAS PELAYANAN DAN KEPUASAN PASIEN DENGAN LOYALITAS PASIEN LAYANAN UNGGULAN DI RS DR. TADJUDDIN CHALID MAKASSAR TAHUN 2024 - Chaerunnisa, Chaerunnisa (Journal of Innovation Research and Knowledge, 2024)
Dr. Tadjuddin Chalid Makassar Hospital has featured services including medical rehabilitation services, eye services and vascular surgery services. The results of the Community Satisfaction Index (IKM) at RSTC IKM in 2021 were 85.23%, IKM in 2022 was 85.60% and IKM in 2023 was 85.10. The results is in category service point B based on the regulation of Permenpanrb No 14 of year 2017 about the guideliness for community satisfaction surveys for public service unit. The results of the IKM measurement show the patient satisfaction index which is closely related to service quality. Therefore, the problem of patient satisfaction with service quality that affects patient loyalty is important to know to help increase hospital revenue. This study aims to determine the quality of service and patient satisfaction with the loyalty of featured service patients at Dr. Tadjuddin Chalid Hospital, Makassar. The type of research used was analytic observational with a cross sectional study design. The study population was outpatients (polyclinics) at 3 (three) featured services at Dr. Tadjuddin Chalid Hospital Makassar. Sample data were collected from 381 patients through questionnaires. The collected patient data were analyzed univariately and bivariately by conducting the Chi-Square test on the developed hypothesis.  The results of univariate analysis showed that respondents gave good responses on the quality variables of the Tangible dimension (100%), and Reliability (97.6%), Responsiveness (98.2%), Assurance (99.7%), Emphaty (96.3%). In the satisfaction variable, the Ancillary Service dimension (97.6%), Medical Service (97.1%), and Price (99.7%) and the Loyalty dimension (98.7%). The results of bivariate analysis show that there is a significant relationship between service quality and patient loyalty (p-value = 0.000 <0.05) and a significant relationship also occurs between patient satisfaction and patient loyalty (p-value = 0.000 <0.05). Conclusion: The results of this study indicate a significant relationship between service quality and patient satisfaction with patient loyalty in featured services. Hospital management can increase patient loyalty to the featured services of Dr. Tadjuddin Chalid hospital by improving service quality and patient satisfaction